Armazenamento de sementes de talisia esculenta (A. St. Hil) Radlk. - Silva, Maria Lúcia Maurício da (2015)
The pitombeira [Talisia esculenta (A. St. Hil) Radlk] is found within primary dense forests and secondary formations, usually in alluvial floodplains and valley floor for almost all of Brazil, whose fruits are highly appreciated and sold in fairs free and supermarkets in the North and Northeast regions. Despite its importance, there is no technology that allows the storage of the seeds for long periods, so the aim of this study was to evaluate the emergence and early growth of T. esculenta seedlings grown from seeds under different storage periods. The study was conducted in Agricultural Science Center of Seed Analysis Laboratory of the Universidade Federal da Paraíba, Areia-PB. Before being stored, the seeds were dried for 0 (without drying), 6, 12, 18 and 24 hours to give the water content of 45,70; 43,90; 41,40; 40,98 and 39,88%, respectively. Then we were packed in polyethylene bags (with a capacity of 1 kg) and stored in domestic refrigerator (6 ± 2 ° C) for up to 60 days, with evaluations conducted initially and every ten days of storage. In evaluating the effect of treatment was determined the water content of the seeds, emergency, first count and emergence rate, as well as length and seedling dry matter. The experimental design was completely randomized with treatments arranged in a factorial 5 x 7 (water content and storage periods), with four replications of 25 seeds. The interaction between the factors water content and storage periods was significant for all variables except for the content of the seeds and water. The percentage and seedling emergence speed were negatively affected by the storage according to the water content of the seeds. Seeds packed in polyethylene bags with water content of 39,88 to 41,40%, stored for up to 40 days in the refrigerator remains viable without significant loss of viability and initial force